The disproportionality of ethnic minority teachers in England: trends, patterns, and problems [version 2; peer review: 3 approved, 1 approved with reservations] - Wenqing Chen; Stephen Gorard; Beng Huat See; Yiyi Tan; Antonina Tereshchenko; Carolina Gazmuri; Nadia Siddiqui; Feyisa Demie (Routledge Open Research, 2023)
Background: England has an ethnically diverse population; reflected in the teacher workforce, and the student body in schools. However, it is not clear that these figures are in proportion to each other. This paper examines the ethnic profile of students and their teachers and considers their geographical distribution. Methods This paper uses existing aggregated official publicly available datasets to describe the patterns and trends in the proportion of ethnic minority teachers compared to ethnic minority pupils in England 2015-2021. Data comes from the Department for Education (DfE), the University and Colleges Admissions Service (UCAS), the Organisation for Economic Co-operation and development (OECD/TALIS), and the Office for National Statistics (ONS). Results We found that there are proportionately more White British teachers than in the student intakes to schools. This disproportion (where there are more White British teachers among teachers than there are White British pupils among pupils) is worse for promoted school leaders like deputies and headteachers than it is for classroom teachers. In London, due to the exceptional number of ethnic minority students, the disproportion (or mismatch) is worse in London than anywhere else. Areas with the fewest ethnic minority pupils (and teachers), like the North East, have the most proportionate workforce (in this limited sense). Conclusions A student lacking any teachers of the same ethnic group might be treated differently at school, and there is some evidence that this might affect their attainment outcomes. The lack of ethnic diversity in some schools and areas, regardless of proportions, may impoverish the diversity of the whole school system. Several possible reasons for these patterns are noted in the paper, but it is clear that ethnic minority applicants to teacher training are less likely to be accepted, and less likely to obtain qualified teacher status or an eventual teaching post.